2020
DOI: 10.21470/1678-9741-2019-0473
|View full text |Cite
|
Sign up to set email alerts
|

Extrapleural Closure of Patent Ductus Arteriosus: How We Do It

Abstract: Patent ductus arteriosus (PDA) is a clinical condition mostly found in premature newborns. Among several medical, surgical and interventional treatment options, extrapleural ligation through a left minithoracotomy is recognized as a safe, efficient and less expensive technique. In fact, it requires short surgical times, grants good exposure of the duct and nearby structures ( e.g. , thoracic duct, left recurrent laryngeal nerve), and avoids pleural space opening and subsequent pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…The second sound of the pulmonary valve is hyperactive, but it is often obscured by loud murmurs. In patients with larger shunt volume, diastolic murmur due to relative mitral stenosis can be heard in the apical region [7,8]. Blood pressure measurement showed that systolic blood pressure was mostly in the normal range, while diastolic blood pressure was decreased, so pulse pressure was widened, and limb blood vessels have water pulse and shooting sound.…”
Section: Introductionmentioning
confidence: 99%
“…The second sound of the pulmonary valve is hyperactive, but it is often obscured by loud murmurs. In patients with larger shunt volume, diastolic murmur due to relative mitral stenosis can be heard in the apical region [7,8]. Blood pressure measurement showed that systolic blood pressure was mostly in the normal range, while diastolic blood pressure was decreased, so pulse pressure was widened, and limb blood vessels have water pulse and shooting sound.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical ligation uses titanium clamps; early surgical ligation minimizes the side effects of HS PDA and is more commonly used in low birth weight premature infants (7). The method of extrapleural surgical plasty of PDA is inexpensive and effective, with good cosmetic results, and is also more often used in premature infants (8). Gianturco coils have been used for small to medium diameter PDA with good postoperative results.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has some complications, such as pleural effusion or phrenic nerve damage, an extrapleural or video-assisted minimally invasive surgery have been described for the closure of PDA in critically ill patients [Früh 2011;Wyss 2005;Mazzera 2002;Vicente 2004;Iwase 2003;Leon-Wyss 2003;Pradegan 2020;Sersar 2005;Demirturk 2011;Chen 2011;Villa 2004]. No report has been published concerning PDA closure in combination with coarctation repair in the same session using an extrapleural technique in neonates or infants with congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…With surgical experiences and technological advancement, successful trans-and extrapleural or minimally invasive (endoscopic) surgical approaches may prevent late complications such as scoliosis, winged scapula, chest wall deformities, breast malformation, and rib fusion after the transpleural technique, which also may cause secondary respiratory compromise. The advantage of an extrapleural technique has been described in a limited number of patients [Wyss 2005;Mazzera 2002;Vicente 2004;Iwase 2003;Leon-Wyss 2003;Pradegan 2020;Sersar 2005;Demirturk 2011].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation